18. Delivery analysis, a useful tool for adaptive radiotherapy in Tomotherapy?. (December 2017) - Moignier, A.; Huger, S.; Marchesi, V.; Guinement, L.
Abstract : Introduction: One of the assets of tomotherapy is the presence of a MVCT detector. It can be used for pre-treatment quality control, or during treatment, for acquiring positioning images and sinograms related to the post-patient fluence. For an adaptive radiotherapy approach, the study aim was to define metrics and alert thresholds, in order to identify the necessity for re-planning based on another CT scan. Methods: Ten head-and-neck treatments having been re-planned, were included in this study. For five of them, it was due to a tumor shrinking, the others were related to a positioning issue, with potential morphological differences. Analyzed data were the fusion between the simulation CT images and the MVCT images, and the MVCT detector sinograms for each fraction. The analysis was performed with Delivery Analysis (Accuray) to quantify the gamma index between the sinograms of a given fraction and a reference one, and the percentage of detectors having less than 5% of difference between two fractions ("score5%"). Then, the alert thresholds were assessed with five records of brain tumors, known to be without morphological modifications during the treatment. Consequently, if the alert thresholds are suited for, none of them should be reached for these records. Results: Among the ten head-and-neck records, four of them had gamma index (3%/3 mm) inferior to 97%, with one inferior to 95%, before re-planning. All records had "score5%" inferior to 80%, with nine inferior to 70%. The level 1/level 2 alert thresholds were set to: 97%/95% for the gamma index (3%/3 mm) and 80%/70% for the "score5%". The five records of brain tumors had gamma index (3%/3 mm) scores ranging between 99% and 100%, and " score5% " superior to 80%. Conclusions: Alert thresholds were defined to identify records that potentially require a re-planning. They only indicate the necessity for a morphological analysis of the images to estimate the origin of the differences and their potential consequences on the treatment, before acquiring a new CT scan for re-planning. These thresholds are currently applied in a prospective aim, in order to confirm their interest on a larger database. This study is also extended to other locations, such as anal canal treatments.